A Network Perspective and Hidden Corruption - Osifo, Omoregie Charles (Macrothink Institute, 2018)
This study examines the hidden aspects of corruption from a network perspective. Through networking, we understand the nature and functioning of hidden corruption, because hidden corruption relates to various acts of corruption that are difficult to observe and prosecute legally. The dimensions to understand hidden corruption are structural and institutional corruption, distorted network, and grey corruption. Different types of illegal, criminal, or unethical networks are understood through two dimensions (structural and institutional corruption and distorted network) of hidden corruption. Grey corruption is another dimension of hidden corruption, but has no defined network existence. The main types of hidden, unethical and criminal networks that exist around the world are greed-oriented institutional network, old-boy network, and clandestine network. Emphases on digital expertise and reforms targeting attitudinal, cultural, legal, and institutional changes have been identified as ways of addressing the phenomenon of hidden corruption from a contemporary standpoint, because of emerging events/realities.
Keywords: network theory; hidden corruption; structural and institutional corruption; distorted network; fi=Julkisjohtaminen|en=Public Management|